L’autoreprésentation de femmes en conflit : les récits d’emprisonnement des suffragettes - Christian Auer (Anglophonia)
Between 1905 and the beginning of World War I around a thousand suffragettes were imprisoned because of their political activities. The conflict between the suffragettes and the government reached its climax in 1909 when some of the imprisoned suffragettes decided to go on hunger strike to obtain the status of political prisoners. Constance Lytton’s Prisons and Prisoners and Annie Kenney’s Memories of a Militant feature among the most interesting narratives that were written by imprisoned suffragettes.Although it should be kept in mind that Prisons and Prisoners and Memories of a Militant are subjective constructions written by dedicated activists, the two narratives provide some fundamental information on the prison conditions of the suffragettes. The two texts also indicate that the suffragettes were ready to take up any form of action that would enable them to challenge the patriarchal ideology of the time.Prisons and Prisoners and Memories of a Militant also shed some light on a time when the relations between genders were characterised by the passage from authority to power or from consensus to coercion.